The Values of Heroism As Seen in Rick Riordan’s The Lost Hero - Amirudin, Andy; Mendrofa, Hilde Riang (Jurnal Ilmiah Pendidikan Scholastic, 2025)
This research is entitled “The Values Heroism As Seen In Rick Riordan's The Lost Hero”. This research discusses the values of heroism as well as the stages of the hero's journey experienced by Jason as seen from the novel The Lost Hero. This research uses a descriptive qualitative method. In obtaining data, it is done by analyzing each heroism value based on the concept of heroism values, and describing each stage of Jason's journey according to Campbell's hero's journey theory. Jason's heroism values based on the results of the research consist of courage, have faith in one own abilities, work hard and never give up, integrity, and tolerance. Meanwhile, the stages of the hero's journey in this novel show that Jason has gone through three major stages out of seventeen steps. Five steps from the departure stage, six steps from the initiation stage, and six steps from the return stage. This leads to the conclusion that the main character has five points of heroism values in himself and the ability to complete seventeen stages of the journey as theorized in the hero's journey by Campbell.